Does A Regional Trade Agreement Lessen or Worsen Growth Volatility? An Empirical Investigation - Roland Kangni Kpodar; Patrick Imam (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
This paper assesses how regional trade agreements (RTAs) impact growth volatility on a worldwide sample of 170 countries with data spanning the period 1978-2012. Notwithstanding concerns that trade openness through RTAs can heighten exposure to shocks, in particular when it leads to increased product specialization, RTAs through enhanced policy credibility, improved policy coordination, and reduced risk of conflicts can ease growth volatility. Empirical estimations suggest the benefits outweigh the costs as RTAs are consistently associated with lower growth volatility, after controlling for trade openness and other determinants of growth volatility. Furthermore, regression results also suggest that countries that are more prone to shocks are more likely to join a RTA, in particular with countries with relatively less volatile growth, additionally enhancing the stabilization effect.
Keywords: F13; F15; F43; 330